ANALISIS PENGARUH SIZE, MARKET TO BOOK VALUE, BETA, DAN MISPRICING TERHADAP RETURN SAHAM (Studi kasus perusahaan yang terdaftar dalam Indeks LQ45 periode 2010-2013) - Anindyaguna, Bhagas; Arfianto, Arfianto (Diponegoro Journal of Management, 2014)
Stock market is a place that is used to perform transactions and / or purchasing securities as well as an effective means to accelerate economic growth. Stock market isalso a place to allow the peopleto make long term investments so that funds can be channeled into productive sectors. When the investor making investment, they will consider two main things, namely the expected results (expected return) and investment risk. Rational investors will always seek to obtain information and perform various analysis to reduce the uncertainty in the investment or to reduce existing risks. This study was conducted to determine the effect of size, price-to-book value, beta and mispricing on stock returns. The data used in this study was company data incorporated in LQ 45 during the period 2010-2013. This research was conducted with quantitative methods on the financial statements of listed companies in the LQ 45 during the period 2010-2013. The total study sample was 44 companies listed in LQ 45. These 44 companies determined by purposive sampling method. The method of hypothesis testing using different test t-test and multiple linear regression analysis.The results showed a positive and significant effect size on stock returns. Market to Book Value show positive effect and significant to stock returns. Beta show positive effect and significant on stock returns. The variance ratio show negative effect and significant negative effect on stock returns or stock mispricing positive impact and significant on stock returns